ANALISIS PROSES PERMESINAN PADA PRODUKSI MESIN JIG MENGGUNAKAN PENDEKATAN LEAN AND GREEN - Gerasimos Anggoro Priosudarmo (2021)
PT. XYZ is an industry that is engaged in the manufacture of jig machines. This industry uses a lot of machining tools such as welding, cnc milling machines and cnc lathes to making its products. The results of my observations and field studies at PT. XYZ shows that in the process of making the jig machine PT. XYZ has waste that has the potential to pollute the environment. Identification of waste at PT.XYZ uses the fishbone method, 5 whys which is a tool from lean and then integrated with life cycle analysis (Life Cycle Assessment). This integration is carried out to process the jig machine product so that an alternative or idea can be identified that aims to provide added value from a waste, while the Life Cycle Assessment (LCA) with the Simapro 9.1 application aims to evaluate the environmental impact of a product and reduce liability. (liabilities) to the environment.